The agenda setting hypothesis in the new media environment - Aruguete, Natalia (2017)
The aim of this paper is to review the literature that discusses the basic premises of theoretical and empirical studies on Agenda Setting theory, and to propose a “new frontier” in the relationship between traditional elite media and new media. The objective is to explore the extent to which the dynamics of the flow of information created in new media –particularly in blogs and Twitter– is distorting the boundaries of the traditional postulates of this theoretical perspective